Perfusion-based ex vivo culture of frozen ovarian cancer tissues with preserved tumor microenvironment - Monica De Luise; Ivana Kurelac; Sara Coluccelli; Antonio De Leo; Ewelina M. Bartoszek; Maria Iorio; Marco Grillini; Camelia Alexandra Coadă; Dario de Biase; Lorena Marchio; Mónica Núñez López; Natalie Rimmer; et al. (npj Precision Oncology)
Abstract Ovarian cancer (OC) poses significant treatment challenges due to late-stage diagnosis and a complex tumor microenvironment contributing to therapy resistance. We optimized a U-CUP perfusion-based bioreactor method to culture patient-derived primary and metastatic OC specimens, demonstrating that perfusion better preserves cancer cell viability and proliferation, both when fresh and slow-frozen tissues were used. Perfused cultures maintained key microenvironment components, including cancer-associated fibroblasts, endothelial and immune cells. Genetic analysis confirmed the retention in culture of tumor-specific driver mutations. We hence challenged ad hoc generated cisplatin-sensitive and resistant OC cells with cisplatin during growth in U-CUP, validating our system for the testing of drug response. Finally, treatment of slow-frozen OC tissues with carboplatin/paclitaxel revealed different degrees of response to treatment, as indicated by variations in tumor necrosis and number of residual PAX8+ cells, providing the bases for the prompt evaluation of OC standard chemotherapy efficacy in our ex vivo system.